Hydrothermal Synthesis and Performance of Li 4 Ti 5 O 12 and Sn Composite as Anode Material for Lithium Ion Battery - Widhiatmaka Widhiatmaka; Guntur Tri Setiadanu (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Lithium titanate (Li4Ti5O12) and tin (Sn) composites are successfully prepared by hydrothermal synthesis. The objectives of this research were to obtain a spinel structure of LTO at a calcination temperature of 500C, and to improve performance of LTO by addition of Sn. The thermal, crystal structure, microstructure and electrical properties of the samples have been characterized by DT/TGA, XRD, SEM/EDX, and EIS, respectively. Meanwhile, electrochemical properties were analyzed using a charge-discharge battery analyzer. The results showed that the spinel phase was obtained for  LTO 500oC and 10%Sn composite with the highest conductivity value of  9.06 x 10-7 S/cm. Cyclic voltammetry test showed a couple of anodic-cathodic reduction-oxidation (redox) voltages at 1.48V and 1.74 V for  LTO and at  1.65 V and 2.11 V for TiO2. Lithiation voltage for Sn occurred at 0.61 V. The charge/discharge test of LTO 500oC and 10%Sn composite showed that the addition of Sn exhibited capacity at  low current-voltage (0.6 V), identifying the advantages of composite which still had discharge capacity at low voltage. The specific capacity for LTO 500oC and 10%Sn composite increased from 76 to 110 mAh/g at 0.3C rate. And the spinel LTO sample can work up to 60C rate.